Strengthening Islamic financial literacy through waqf education: A community service initiative at Zammi Yatim and Dhuafa School, Medan - Hubbul Wathan; Selfi Afriani Gultom; Ismi Afandi; Rezha Destiadi; Sudarsono Sudarsono (Nur Science Institute, 2026)
This community service program aimed to strengthen waqf and Islamic financial literacy among teachers at ZAMMI School for Orphans and the Underprivileged in Medan through participatory and technology-based training. The program was implemented through socialization sessions, training on digital teaching media, mentoring, and the provision of basic educational technology tools. Eight teachers participated in the program. The implementation of this community service program (PKM) uses a participatory mixed-method approach, combining both qualitative and quantitative data to gain a comprehensive understanding of the improvement in waqf and Islamic financial literacy among teachers. Evaluation was conducted using observations, interviews, and pre- and post-training questionnaires. The results indicated a substantial improvement in teachers’ understanding of waqf and Islamic finance, as well as increased confidence in utilizing digital media for learning. Quantitatively, the average literacy score increased from 3.34 to 4.45, indicating a significant positive change after the intervention. More importantly, teachers began to integrate waqf values and Islamic financial concepts into learning activities and school-based philanthropic practices.